Compact Four-Port Dual-Sense Circularly Polarized Stack-Up Patch Antenna for UHF/MW-RFID MIMO System - Enze Zhang; Jinghui Qiu (International Journal of Antennas and Propagation)
A four-port dual-band dual circularly polarized (CP) stack-up patch antenna is introduced for multiple-input-multiple-output (MIMO) RFID application. The proposed antenna adopts two FR 4 substrates and one Rogers Ro4350b substrates. Two pairs of isolated ports work at FCC UHF/MW-RFID bands (0.902–0.928 and 2.4–2.485 GHz) with port isolations of 20 dB and 25 dB, respectively. Four inverted-F radiating elements fed with a 90° phase-delay feeding network realize the CP radiation at the FCC UHF-RFID band (0.902–0.928 GHz). The corner-truncated square slot and patch are implemented to obtain CP modes at the MW-RFID band. The relative impedance bandwidths in the FCC UHF and MW band are 10.9% and 9.4%, respectively, with peak gains of 4.1 and 7.2 dBic. The antenna’s MIMO performance of envelope correlation coefficient (ECC) is lower than 0.01, and diversity gain (DG) is close to 10 dB. Thanks to the stack-up configuration, the dual-band RFID antenna realizes good antenna performance with a compact size of 0.6 × 0.6 × 0.07 λ3.